Русская советская литературная критика (1956-1983): хрестоматия / Л. Ф. Ершов, В. П. Муромский - Ершов Л. Ф. (Просвещение, 1984)
Экземпляры: (20181205) / Инвентарный номер: 12509 / Цена: 1.20 / Сис.шифр: 83.3Р7 / Авт.знак: Е80 / ББК: 83.3Р7